2018
DOI: 10.3399/bjgp18x697649
|View full text |Cite
|
Sign up to set email alerts
|

Delivery and impact of the NHS Health Check in the first 8 years: a systematic review

Abstract: Published attendance, uptake, and prescribing rates are all lower than originally anticipated, and data on impact are limited, with very few studies reporting the effect of attendance on health-related behaviours. High-quality studies comparing matched attendees and non-attendees and health economic analyses are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 32 publications
(131 reference statements)
3
40
0
Order By: Relevance
“…Data on impact are limited but have shown a small increase in disease detection, statin and anti-hypertensive prescriptions and a small decrease in modelled CVD risk. 186 A systematic review of 31 studies using multiple health behaviour changes in primary care to reduce cardiovascular risk in people without established CVD found a modest, statistically significant effect on individual behaviours and overall cardiovascular risk. 187 A meta-analysis of prospective controlled cohort studies and retrospective controlled cohort studies published since 1995 confirmed the efficacy of CR on cardiac prognosis even in the era of statin therapy and acute revascularisation.…”
Section: Clinical Settingsmentioning
confidence: 99%
“…Data on impact are limited but have shown a small increase in disease detection, statin and anti-hypertensive prescriptions and a small decrease in modelled CVD risk. 186 A systematic review of 31 studies using multiple health behaviour changes in primary care to reduce cardiovascular risk in people without established CVD found a modest, statistically significant effect on individual behaviours and overall cardiovascular risk. 187 A meta-analysis of prospective controlled cohort studies and retrospective controlled cohort studies published since 1995 confirmed the efficacy of CR on cardiac prognosis even in the era of statin therapy and acute revascularisation.…”
Section: Clinical Settingsmentioning
confidence: 99%
“…Cost-effectiveness calculations for this programme were based on an assumed uptake of 75% of all those eligible [ 2 ]. However, since 2013 when delivery of NHS Health Check became a statutory responsibility of local authorities, < 50% of those eligible have received a NHS Health Check [ 3 ]. Improving the effectiveness and uptake of the programme is a key part of PHE’s strategic priority around predictive prevention to better predict and prevent poor health.…”
Section: Introductionmentioning
confidence: 99%
“…Second, by screening children, FH is identified before the onset of clinical disease providing the opportunity for prevention in children, their siblings and their parents (median age 32 in the demonstration project) [8]. Electronic health records in adults are a potential supplement to identifying new FH index cases but largely miss the preventive opportunity (median age at an NHS Health Check is about 60 years) [22].…”
Section: Discussionmentioning
confidence: 99%